Effects of a myotoxic phospholipase A2 isolated from Bothrops asper venom on skeletal muscle sarcoplasmic reticulum - Gutiérrez, José María (1987)
The myotoxin from B. asper snake venom inhibited Ca-ATPase activity of rabbit sarcoplasmic reticulum after incubation in vitro. Inhibition was non-competitive and albumin enhanced the effect of the toxin. Furthermore, B. asper myotoxin hydrolyzed sarcoplasmic reticulum phospholipids and induced a dose-dependent release of horseradish peroxidase that had been trapped in sarcoplasmic reticulum vesicles. Binding studies indicated that myotoxin does not bind to any particular protein of this membrane, suggesting that the toxin might interact with phospholipids. Inhibition of Ca-ATPase is probably a consequence of an alteration in sarcoplasmic reticulum phospholipids.